Electrochemical Mechanical Properties of Beam-Column Joints of Building Steel Structures under Impact Loads - Liu Qian (Journal of Chemistry)
To optimize the seismic performance in high-rise buildings, the performance changes of beam-column joints of high-rise steel structures of buildings when they are impacted are analyzed to obtain the optimal choice of joint combination. The most commonly used steel beam and steel column joints are selected as the research objects. Firstly, the finite element model and the shell element model of the force are established and then the model of the finite element combination of six kinds of steel beam and steel column joints is established. Secondly, the applied data of common impact force in actual buildings are collected, and the simulated impact force in this experiment is established according to the sampled data. Then, the changes in each performance of the joints under the action of the impact external force are deeply explored through simulation. Finally, the accuracy of the model is confirmed by calculation. The experimental results comprehensively show that the transmission mechanisms of the impact force are different for the six joints. Through calculation and comparison, the bending stiffness, strength, deformation, the displacement degree of the joints, and the bearing degree of the impact external force are comprehensively analyzed. It is concluded that the bolt-type and external diaphragm-type steel tube column concrete and steel-beam concrete composite joints have better seismic resistance than the other five joints. The bolt-type does not need to be welded on site, and the on-site construction workers only need to assemble, which can reduce the technical requirements for construction workers, improving the practicability and applicability. Therefore, it shows reliable reference significance for the joint selection of building steel structures.